PENGARUH KEBIJAKAN KOMPENSASI TERHADAP KINERJA APARAT KEPOLISIAN (Suatu Studi Di Polres Kota Bitung) - DAVID, PRICILYA CHRISTIN; Mandey, Jantje; Dengo, Salmin (Sam Ratulangi University, 2015)
Abstrack; Police compensation policy in the current environment is expected to boost theperformance of the police. The aim of research to determine the effect of compensation policies on theperformance of police officers at the police station Bitung.This study uses quantitative methods. Sample of respondents were taken with stratified randomsampling technique (based on class rank) of 10% (50 people) of the population (504 police officers Bitung).Collecting data using questionnaires / questionnaire and assisted with interview techniques. The analysistechnique used is the inferential statistical analysis is linear regression and correlation product moment.The result showed: (1) the regression coefficient of variable compensation policies on theperformance of police officers Bitung is posifive and significant. (2) the correlation coefficient and thecoefficient of determination variable compensation policies on the performance of police officers was highand significant Bitung.Based on the results of the data analysis is concluded that the compensation policy Polri positive andsignificant impact on the performance of police officers at the police station Bitung.Departing from the conclusions of the study results suggested: (1) compensation policy within thepolice force now needs to be continued, but there needs to be improvement in some kind of allowance. (2)Improvement in environmental compensation National Police must be balanced or accompanied by anincrease in performance of the members / officers. Therefore, each member / police should be trying to fix orimprove performance.Keywords: Compensation Policy Police, Police Of Performance